Medication adherence and blood pressure control among hypertensive patients in Salyan Hospital - Sharma, Pradeep; Shrestha, Bikas (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Hypertension is a chronic medical condition with severe consequences and it remains  inadequately managed everywhere. Medication adherence is a critical parameter for achieving strict blood  pressure control in patients undergoing antihypertensive therapy. Good medication adherence is also a key  factor determining the success of preventive measures for cardiovascular risk reduction. So, we aimed to study  the medication adherence and blood pressure control among hypertensive patients of Salyan Hospital.Method: A cross-sectional observational study was conducted in Salyan Hospital. Total of 110 adult  hypertensive patients were enrolled in the study. A structured questionnaire i.e. Morisky medication  adherence questionnaire (MMAS-8) in Nepali version was used to measure adherence. In addition, WHO validated method of measuring BP, drug type used and type of therapy were also included. Data were entered  and analyzed using IBM SPSS.Result: Out of 110 respondents enrolled, less than half of the respondents 45.45% had controlled BP. More  than 4/5th were on monotherapy. BP control in monotherapy was 47.87% and in combination therapy was  45.45%. Patient with high, medium and low adherence were 40.9%, (44.54%) and 14.54% respectively. Level of  adherence to antihypertensive drugs was related to BP control (p=0.0004). Most commonly used antihypertensive were CCBs.Conclusion: There was high prevalence of uncontrolled BP among hypertensive patients in Salyan Hospital.  Similarly, higher number of patients were on monotherapy. But BP control in monotherapy and combination  therapy was similar. Higher number of patients were non-adherent. The relation between BP control and  medication adherence was statistically significant. So the causes of poor BP control and poor adherence should be explored and addressed in each doctor-patient encounter.